If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(7 + z) = 45 (7 * 9 + z * 9) = 45 (63 + 9z) = 45 Solving 63 + 9z = 45 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 9z = 45 + -63 Combine like terms: 63 + -63 = 0 0 + 9z = 45 + -63 9z = 45 + -63 Combine like terms: 45 + -63 = -18 9z = -18 Divide each side by '9'. z = -2 Simplifying z = -2
| -3z+9z-7=29 | | x+31=40 | | 9(x+1)+3(7-6x)=16x | | 13y-8y-4=56.20 | | 0=-.25x+6 | | x-0.6=0.4 | | 4y+-3y-6=1 | | 3x-7=10-2x | | 6x+3=8x-11 | | r+(-29)=-38 | | x-1/4=1/8 | | 3(2+x)=0 | | 7d+5d+4d-4= | | x^2-3x+1-x^2+2x+7= | | 2(x-3)-4x=-10 | | -4(9+z)=-52 | | 5b=75 | | x-0.9=0.3 | | f(x)=3(x-2)+7 | | 2a+2=a-10 | | 6y+-2y-7=9 | | 9+8x=-5+x | | 2z+-2z+4=4 | | 7(9+z)=91 | | px(q+5)= | | x+1.2=0.6 | | 9z+7z-5=43 | | 4z+-3z+2=-2 | | p+7=-2 | | y=-5+-15 | | 5x-x-7=29 | | 100x=5580 |